Physical parameters and risk factors associated with the elimination of Arabian and crossed Arabian endurance horses during a 120-km endurance race - Adamu, Lawan; Mohd Adzahan, Noraniza; Abdullah, Rasedee; Fateh Mohamed, Bashir Ahmad (W.B. Saunders, 2014)
Endurance racing is one long-distance event among the equine sporting activities associated with severe injuries and metabolic derangements that impede the health status of horses participating in the event. Therefore, this study evaluated the physical parameters and risk factors associated with the elimination of Arabian and crossed Arabian endurance horses during a 120-km race. Fifty-three Arabian and crossed Arabian endurance horses aged 6 to 15 years old participated in an endurance race of 120 km. All the horses were examined and found fit according to Fédération Équestre Internationale (FEI) regulations. After the endurance race 14 Arabian endurance horses completed the race successfully while 31 Arabian and crossed Arabian were eliminated. Their speed and heart rates were significantly higher (P < .0001). There were significant differences in skin recoil (P < .0395), color of mucous membrane (P < .0189), intestinal motility (P < .0124), and capillary refill time (P < .0082). There also were significant differences in age (P < .0018), breed (P < .0119), and equine establishments (P < .0205) among the eliminated horses and the Arabian and crossed Arabian endurance horses that successfully completed the race. In conclusion, the physical parameters and risk factors were significantly associated with the elimination of Arabian and crossed Arabian endurance horses. Therefore, close monitoring of the physical parameters and risk factors are essential in order to improve the performance of Arabian and crossed Arabian horses, and further studies are required on other associated parameters.